Macrophage-Mediated Glial Cell Elimination in the Postnatal Mouse Cochlea - Brown, LaShardai N.; Xing, Yazhi; Noble, Kenyaria V.; Barth, Jeremy L.; Panganiban, Clarisse H.; Smythe, Nancy M.; Bridges, Mary C.; Zhu, Juhong; Lang, Hainan (Frontiers in Molecular Neuroscience, 2017)
Hearing relies on the transmission of auditory information from sensory hair cells to the brain through the auditory nerve. This relay of information requires hair cells to be innervated by spiral ganglion neurons (SGNs) in an exclusive manner and for SGNs to be ensheathed by myelinating and non-myelinating glial cells. In the developing auditory nerve, mistargeted SGN axons are retracted or pruned and excessive cells are cleared in a process referred to as nerve refinement. Whether auditory glial cells are eliminated during auditory nerve refinement is unknown. Using early postnatal mice of either sex, we show that glial cell numbers decrease after the first postnatal week, corresponding temporally with nerve refinement in the developing auditory nerve. Additionally, expression of immune-related genes was upregulated and macrophage numbers increase in a manner coinciding with the reduction of glial cell numbers. Transient depletion of macrophages during early auditory nerve development, using transgenic CD11bDTR/EGFP mice, resulted in the appearance of excessive glial cells. Macrophage depletion caused abnormalities in myelin formation and transient edema of the stria vascularis. Macrophage-depleted mice also showed auditory function impairment that partially recovered in adulthood. These findings demonstrate that macrophages contribute to the regulation of glial cell number during postnatal development of the cochlea and that glial cells play a critical role in hearing onset and maturation.